At the time of the Comintern Congresses. On the balustrade above the Moskva River, on the background the Kremlin. Kollontaj at the right, on her side Roland Holst-van der Schalk. The two others are unknown
At the time of the Comintern Congresses. On the balustrade above the Moskva River, on the background the Kremlin. Kollontaj at the right, on her side Roland Holst-van der Schalk. The two others are unknown.